Moni Odigitria : a prepalatial cemetery and its environs in the Asterousia, southern Crete - Vasilakēs, Antōnēs (Prehistory monographs, 2010)
Survey of the environs around the Tholos Cemetery /Keith Branigan and Andonis Vasilakis --Appendix : The Roman pottery /Jane Francis --Excavation and architecture of the cemetery /Andonis Vasilakis --The pottery assemblage : data and analysis /Keith Branigan and Tim Campbell-Green --Interpretation of the pottery assemblage /Keith Branigan and Tim Campbell-Green --Metalwork /Keith Branigan --Of blades and burials, flakes and funerals : the chipped stone from Moni Odigitria /Tristan Carter --Stone vases and tools /Doniert Evely --Jewelry and other small finds /Flora Michelaki and Andonis Vasilakis --Seals from the cemetery /Kostas Sbonias --Analysis of the human bones /Sevi Triantaphyllou --History and use of the cemetery /Keith Branigan --The Hagiopharango in the early Bronze Age /Keith Branigan and Andonis Vasilakis --[To come] /Andonis Vasilakis --Concordance A : Omades, trenches, areas, and strata from the 1980 excavation of Tholos B --Concordance B : Herakleion Museum numbers and catalog numbers for all types of objects --Concordance C : Catalog and Herakleion Museum numbers for all types of objects.